GROWTH OF TiO2:Co/TiO2/TiO2:Co and TiO2:Co/Si(100) FERROMAGNETIC SEMICONDUCTOR THIN FILMS BY MOCVD METHOD AND THEIR APPLICATION IN ELECTRON SPIN INJECTION - SUPRIYANTO (NIM 30203006), EDY
The subject of this dissertation is the growth of TiO2:Co/TiO2/TiO2:Co and TiO2:Co/Si(100) ferromagnetic semiconductor thin films by MOCVD method and use the structure to study the mechanism of electron spin injection. TiO2:Co is a semiconducting ferromagnetic material, also known as diluted magnetic semiconductor (DMS), that has critical temperatures above room temperature. TiO2:Co has both ferromagnetic and semiconductor properties that make it is very potential for spintronic device application. Spintronic devices have excellent characteristics compared to those conventional electronic devices, such as higher speed data processing, smaller device size (compact), and lower energy consumption. Spintronic devices requires DMS material which have Curie temperature (TC) higher than room temperature, a high spin injection efficiency (~100%) and a good compatibility with semiconductor fabrication technology. The MOCVD method has a number of advantages, such as: (1) high growth rate, (2) precise control of composition, (3) conformal step-coverage, and (4) high productivity. This method has not been used for the growth of TiO2:Co/TiO2/TiO2:Co. In this research, TiO2:Co and TiO2 thin films were grown on n-type Si(100) substrates. The optimum growth parameters were used to grow TiO2:Co/TiO2/TiO2:Co structure. A prototype of spintronic device with TiO2:Co/Si(100) structure was fabricated to study the spin transport phenomenon in ferromagnetic semiconductor using the Hanle effect. The structure uses TiO2:Co as a detector or an injector.